Innovations in Mineral Science and Engineering for Sustainable Resource Development - Aditya Sahu; Nidhi Sahu* (International Journal of Minerals, 2026)
The growing global demand for mineral resources, coupled with increasing environmental and social concerns, has intensified the need for sustainable approaches in mineral science and engineering. Traditional mining and mineral processing practices, while essential for industrial development, are often associated with high energy consumption, resource depletion, and environmental degradation. In response, recent innovations in mineral science and engineering have focused on improving resource efficiency, minimizing environmental impact, and ensuring long-term sustainability of mineral resource development. This study presents a comprehensive overview of recent advancements in mineral exploration, extraction, processing, and waste management that contribute to sustainable resource development. Emphasis is placed on advanced exploration techniques, including remote sensing, geophysical modeling, and data-driven approaches, which enhance the accuracy of resource estimation and reduce unnecessary land disturbance. Innovations in mineral processing, such as energy-efficient comminution, selective flotation, hydrometallurgical processes, and bioleaching, have demonstrated significant improvements in metal recovery while lowering energy and water consumption. Furthermore, the integration of digital technologies, including automation, artificial intelligence, and machine learning, has transformed mineral engineering operations by enabling real-time monitoring, process optimization, and predictive maintenance. Sustainable mine design, circular economy concepts, and the reuse of mine tailings and industrial wastes are also discussed as critical strategies for reducing environmental footprints. Advances in environmental management, such as improved tailings storage systems and mine reclamation techniques, contribute to enhanced ecosystem protection and social acceptance. The findings highlight that the future of mineral resource development relies on a multidisciplinary approach that integrates technological innovation, environmental stewardship, and economic viability. Continued research and implementation of sustainable practices in mineral science and engineering are essential to meet global mineral demands while preserving natural resources and ensuring environmental and societal well-being.
Keywords: Critical minerals; Environmental Management; Mineral processing; green mining technologies; mineral engineering; mineral science